PROCEDURE FOR COOPERATION CONTRACT AT PT DEBERSA SUKSES JAYA - Jawak, Elsa Ulina; Amalia, Diah (PT Aksara Indo Rajawali, 2022)
This study report discusses the procedures for implementing the Cooperation contract procedures at PT. Debersa Sukses Jaya. The purpose of this research is to create and compile Standard Operating Procedures for Cooperation Contract Procedures in accordance with the process of establishing cooperation with clients at PT. Debersa Sukses Jaya. This study uses data that has been analyzed using qualitative methods of narrative analysis and the data collection method is carried out by observation and interview techniques. The results of the study stated that an answer was obtained from the identification process for the cause of the client who did not fulfill his responsibilities as a service user, the process of cooperation contract procedures at PT. Debersa Success Jaya, and has created and compiled Standard Operating Procedures for Cooperation Contract Procedures at PT. Debersa Success Jaya.